2010
DOI: 10.1021/jp100923f
|View full text |Cite
|
Sign up to set email alerts
|

Mercury-Mediated Attachment of Metal-Sandwich-Based Altitudinal Molecular Rotors to Gold Surfaces

Abstract: Gold surface attachment of altitudinal molecular rotors provided with ten -HgSCH 2 CH 2 SCH 3 "tentacles" has been monitored with ellipsometry, scanning tunneling microscopy, and X-ray photoelectron spectroscopy (XPS). The rotors appear to adsorb on the gold surface in the intended orientation, with rotor axle parallel to the surface, without any inclination for multilayer growth. According to XPS data, the sulfur-containing tentacles start to be detectably oxidized within hours of exposure to air and can be u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 64 publications
1
20
0
Order By: Relevance
“…We had hoped to prepare the bromo-analogue of 5 directly from 1 by reaction with N-bromosuccinimide and dibenzoylperoxide or azobisisobutyronitrile (AIBN), but both reactions failed. 5 proved an excellent precursor for the triphenyl phosphonium salt [7]Cl, but it failed to react with P(OEt) 3 . The HornereWadswortheEmmons reagent 6 [25] was obtained in the same way as its ferrocene counterpart [26] by a modification of the basic Michaelis reaction [27] in which Na[P(O)(OEt) 2 ] is reacted with the alcohol 4.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…We had hoped to prepare the bromo-analogue of 5 directly from 1 by reaction with N-bromosuccinimide and dibenzoylperoxide or azobisisobutyronitrile (AIBN), but both reactions failed. 5 proved an excellent precursor for the triphenyl phosphonium salt [7]Cl, but it failed to react with P(OEt) 3 . The HornereWadswortheEmmons reagent 6 [25] was obtained in the same way as its ferrocene counterpart [26] by a modification of the basic Michaelis reaction [27] in which Na[P(O)(OEt) 2 ] is reacted with the alcohol 4.…”
Section: Resultsmentioning
confidence: 99%
“…However this has not been reported despite [Fc 3 COH] being first prepared in 1962 [47] and studied intensively more recently [36,39,48], though there have been investigations of the electrochemistry of other multiferrocenyl compounds [45,49]. We were able to carry out our comparison because of a gift of [Fc 3 DE ox ¼ 200 mV). Application of increased anodic potential to [Fc 3 COH] 2þ generates the distinctive adsorption/stripping waveform.…”
Section: Electrochemistrymentioning
confidence: 99%
See 2 more Smart Citations
“…XPS data indicated that the rotors 206 and 208, which contain sulfur containing tentacles start to oxidize within hours of air exposure and can be ultimately removed by washing but the rotor molecules remain firmly attached in the desired orientation due to direct interaction of Hg atoms with the gold surface. Compounds having HgOCOCF 3 as tentacles also adhere to the surface but not always in the desired orientation [86].…”
Section: Scheme 29 Synthesis Of Cosulphos Ligand [33]mentioning
confidence: 99%